Salivary IL17 and IL35 Suppresses Cell Progression in Periodontal Disease Manipulation Induced by TNBs via NF-κB Signaling Pathway: IL17 and IL35 in periodontal disease and systemic osteoporosis - Wang, Yunxiao; Wang, Ling (Progress in Nutrition, 2021)
Background: Periodontal disease prognosis relies primarily on clinical and radiographic parameters. In present study association of interleukins IL17 & IL35 levels in GCF and serum among healthy, gingivitis, and chronic periodontitis (CP) individuals is examined and possibility of using them as possible prognosis marker for periodontal disease activity is explored. Expressions of TNF-α, AKT and NF-κB. Inflammatory cells were evaluated in both cases. Methods: This prospective study was accomplished on patients with osteoporosis and a comprehensive periodontal examination was performed including standardized digital dental periapical radiographs and bone mineral density (BMD) evaluation. ELISA kit was used for quantifying levels of IL-17 and IL-35 in the patients’ plasma. ELISA was used to check expressions level of TNF-α, and NF-κB. Inflammatory cells in both cases. STATA15.0 was used for statistical analysis and a p value ≤0.05 was considered statistically significant. Results: The mean of GI of healthy and osteoporotic group were much lower than periodontitis group. PI, PPD and CAL were almost comparable between healthy control group and osteoporotic group. Plasma IP-17 level and IL35 level where raised in periodontitis group compare to health control and also were significant different from osteoporosis groups. Although IL17 value of osteoporosis group was comparable to health group, IL 35 had significant high value than healthy. Expressions of TNF-α were increased in periodontitis group. Expressions of phosphorylated PI3K and AKT were reduced in periodontitis group. Meanwhile, expressions of NF-κB were decreased periodontitis group compared to systemic osteoporosis. Conclusion: Various studies characterized the host response to infection in periodontal/periapical diseases, they are found to be very different from those of systemic osetoporesis, however this is first to study IL17 and Il35 in such cases. Periodontitis inhibits inflammatory cell process and regulates related factors during pathogenesis, suggesting that through PI3K/AKT/NF-κB signaling pathway disease progression in periodontitis are modulated.